PHOSPHORUS FORMS AND ADSORPTION IN A TYPIC QUARTZIPSAMMENT CULTIVATED WITH SUGARCANE HARVESTED WITHOUT BURNING - Oliveira Filho, José de Souza (2017)
The objective of this study was to evaluate the adsorption of phosphorus (P) and changes in the concentrations of organic and inorganic forms of P in a Neossolo Quartzarênico (Typic Quartzipsamment) after 9 years of successive cultivation with sugar cane without burning to harvest. Therefore, two areas, one in which cane sugar was planted and a native forest reference area, located in the municipality of Paraipaba-CE, were selected. In each area, samples were collected at depths of 0−0.025, 0.025−0.05, 0.05−0.10, 0.10−0.20, and 0.20−0.30 m, and the levels of organic (Po) and inorganic (Pi) phosphorus obtained by sequential extraction, the remaining phosphorus, and the maximum adsorption capacity of phosphorus by the soil were determined. In general, the permanence of straw on the soil surface under sugarcane cultivation promoted the maintenance of Po levels in the surface layers of the profile. The Po accumulated predominantly in the Po fraction extracted with sodium bicarbonate in both areas. Regarding the Pi content, changes were more evident during cultivation due to the effect of successive phosphate fertilizer applications. The fraction extracted with 0.1 mol L-1 sodium hydroxide was the most representative, with the highest levels of P uptake. P adsorption was influenced by the initial content of the nutrient in the soil and no relationship between P adsorption and organic matter content was observed. The highest level of adsorption was observed in the bottom layer of the forest area (133.3 mg kg-1) and the lowest level of adsorption was observed on the surface layer of the area under sugarcane cultivation (59.5 kg mg-1).